Human norovirus inhibition by a human milk oligosaccharide - Koromyslova, Anna D.; Tripathi, Shailesh; Morozov, Vasily; Schroten, Horst; Hansman, Grant S. (Virology, 2017)
Human noroviruses are the leading cause of outbreaks of acute gastroenteritis. Norovirus interactions with histo-blood group antigens (HBGAs) are known to be important for an infection. In this study, we identified the HBGA binding pocket for an emerging GII genotype 17 (GII.17) variant using X-ray crystallography. The GII.17 variant bound the HBGA with an equivalent set of residues as the leading pandemic GII.4 variants. These structural data highlights the conserved nature of HBGA binding site between prevalent GII noroviruses. Noroviruses also interact with human milk oligosaccharides (HMOs), which mimic HBGAs and may function as receptor decoys. We previously showed that HMOs inhibited the binding of rarely detected GII.10 norovirus to HBGAs. We now found that an HMO, 2′-fucosyllactose (2′FL), additionally blocked both the GI.1 and GII.17 noroviruses from binding to HBGAs. Together, these findings provide evidence that 2′FL might function as a broadly reactive antiviral against multiple norovirus genogroups.
Gesehen am 05.09.2018